Technical civilization, boredom and responsibility in Jan Patocka - Ortega Rodriguez, Ivan (Pensando - Revista de Filosofia, 2023)
This article presents Patočka’s analyses of boredom, both in themselves and in relation to his philosophy and -on another plane- to contemporary debates on the topic. Firstly, we present his phenomenological studies of the 1940s, that develop a description of boredom as a mood that, negatively, helps ascertain what fulfilment in human life consists of. Secondly, we present Patočka’s later considerations on boredom as a symptom of deep-seated problems in technical civilisation, as well as the concepts from his philosophy in those years that sustain his positions. Finally, we describe Patočka’s ideas for overcoming the crisis and we consider what these philosophical developments may say to us.This article presents Patočka’s analyses of boredom, both in themselves and in relation to his philosophy and -on another plane- to contemporary debates on the topic. Firstly, we present his phenomenological studies of the 1940s, that develop a description of boredom as a mood that, negatively, helps ascertain what fulfilment in human life consists of. Secondly, we present Patočka’s later considerations on boredom as a symptom of deep-seated problems in technical civilisation, as well as the concepts from his philosophy in those years that sustain his positions. Finally, we describe Patočka’s ideas for overcoming the crisis and we consider what these philosophical developments may say to us.